Analisis Kebutuhan Telur Pada Penjual Jamu Di Kota Bengkulu - lola pitaloka; Johan Setianto; Hardi Prakoso (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2021)
ABSTRACT This study aims to determine the need for eggs of herbal medicine sellers in Bengkulu City. This research was conducted in July 2018, the research method used is a survey method where data collection uses a questionnaire. The variables observed in this study include age, gender, formal education and length of business. Data were analyzed descriptively. The results showed that the overall respondents of herbal medicine sellers in Bengkulu City were male (100%), respondents aged 24-34 were more dominant in selling jamu (40%), had high school education (53.3%), with a length of business of 1 -14 years (46.7%). The eggs needed are 4,860 eggs / week, 19,320 eggs / month and 231,840 eggs / year. Keywords: Needs, Eggs, Herbal Medicine